Two to Tango: Co-evolution of Hominid Natural Killer Cell Receptors and MHC - Wroblewski, Emily E.; Parham, Peter; Guethlein, Lisbeth A. (Frontiers in Immunology, 2019)
Natural killer (NK) cells have diverse roles in hominid immunity and reproduction. Modulating these functions are the interactions between major histocompatibility complex (MHC) class I molecules that are ligands for two NK cell surface receptor types. Diverse killer cell immunoglobulin-like receptors (KIR) bind specific motifs encoded within the polymorphic MHC class I cell surface glycoproteins, while, in more conserved interactions, CD94:NKG2A receptors recognize MHC-E with bound peptides derived from MHC class I leader sequences. The hominid lineage presents a choreographed co-evolution of KIR with their MHC class I ligands. MHC-A, -B and -C are present in all great apes with species-specific haplotypic variation in gene content. The Bw4 epitope recognized by lineage II KIR is restricted to MHC-B but also present on some gorilla and human MHC-A. Common to great apes, but rare in humans, are MHC-B possessing a C1 epitope recognized by lineage III KIR. MHC-C arose from duplication of MHC-B and is fixed in all great apes except orangutan, where it exists on approximately 50% of haplotypes. Recent study showed that gorillas possess yet another intermediate MHC organization compared to humans. Like orangutans, but unlike the Pan-Homo species, duplication of MHC-B occurred. However, MHC-C is fixed, and the MHC-C C2 epitope (absent in orangutans) emerges. This evolution of MHC-C drove expansion of its cognate lineage III KIR. Recently, position -21 of the MHC-B leader sequence has been shown to be critical in determining NK cell educational outcome. In humans, methionine (-21M) results in CD94:NKG2A-focused education whereas threonine (-21T) produces KIR-focused education. This is another dynamic position among hominids. Orangutans have exclusively -21M, consistent with their intermediate stage in lineage III KIR-focused evolution. Gorillas have both -21M and -21T, like humans, but they are unequally encoded by their duplicated B genes. Chimpanzees have near-fixed -21T, indicative of KIR-focused NK education. Harmonious with this observation, chimpanzee KIR exhibit strong binding and, compared to humans, smaller differences between binding levels of activating and inhibitory KIR. Consistent between these MHC-NK cell receptor systems over the course of hominid evolution is the evolution of polymorphism favoring the more novel and dynamic KIR system.